Chapter 6 Beyond embeddedness The next steps - Williams, Clare (Taylor & Francis, 2023)
Embeddedness is the core concept of an economic sociology of law (ESL) lens, but is conceptually confused and inconsistent. We have seen how embeddedness can have a tangible impact on our ability to respond to pressing social dilemmas: financial crashes, social crises, and environmental catastrophes. This chapter enquires into the implications of moving ESL beyond embeddedness, asking if we remove the core concept of the lens, what remains? It then turns to how we might move broader discourse beyond embeddedness-talk, and what this could achieve. Finally, zooming out further, the chapter explores the wider ramifications for how we do, talk, and think about law, economy, and society. In looking forward, the chapter identifies an urgent need for research into the development of natural language processing (NLP) in artificial intelligence (AI), where biases, assumptions, and preferences intrinsic to our conceptual and linguistic tools are at risk of being preserved in digital aspic and placed beyond the reach of future interrogation. Our third fictional persona, Lay Lillian, takes centre stage in this chapter, as she wonders how the insights of previous chapters, explained to her by Academic Ann, can be brought to bear on the problems she is facing.